2022
DOI: 10.2319/100721-749.1
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between malocclusion and history of bullying in vulnerable adolescents

Abstract: Objectives To assess the correlation between malocclusion and a history of bullying. Materials and Methods A cross-sectional study of 494 adolescents aged 12 to 15 years was conducted. The National School Health Survey questionnaire (PeNSE 1 and 2) was used to determine history of bullying by identifying the victim and the abuser. Variables were evaluated based on the individual (age), environment (income, father's and mother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…In order to assess bullying, five studies used the same modified questionnaire from Shaw et al [ 26 ] by Al Bitar et al, in 2013 [ 22 , 28 , 29 , 32 , 33 ], two used the Olweus Bullying/Victim Questionnaire [ 30 , 31 ]; Ramos et al [ 9 ] used the questionnaire used in the National Survey of School Health (PeNSE), Gatto et al [ 7 ] used the Kidscape Questionnaire, Duarte Rodrigues et al [ 34 ] used a question from the CPQ8-10, Bazan-Serrano et al [ 35 ] used a questionnaire from Oliveros et al [ 36 ], Rwakatema et al [ 37 ] used a questionnaire from Ng’ang’a et al [ 38 ] and Onyeaso et al [ 39 ] used a modified questionnaire from Helm [ 20 ]. Seven of the studies used individual arrangement questionnaires [ 20 , 21 , 24 , 40 , 41 , 42 , 43 ], and Alanko et al [ 8 ] used a structured diary.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to assess bullying, five studies used the same modified questionnaire from Shaw et al [ 26 ] by Al Bitar et al, in 2013 [ 22 , 28 , 29 , 32 , 33 ], two used the Olweus Bullying/Victim Questionnaire [ 30 , 31 ]; Ramos et al [ 9 ] used the questionnaire used in the National Survey of School Health (PeNSE), Gatto et al [ 7 ] used the Kidscape Questionnaire, Duarte Rodrigues et al [ 34 ] used a question from the CPQ8-10, Bazan-Serrano et al [ 35 ] used a questionnaire from Oliveros et al [ 36 ], Rwakatema et al [ 37 ] used a questionnaire from Ng’ang’a et al [ 38 ] and Onyeaso et al [ 39 ] used a modified questionnaire from Helm [ 20 ]. Seven of the studies used individual arrangement questionnaires [ 20 , 21 , 24 , 40 , 41 , 42 , 43 ], and Alanko et al [ 8 ] used a structured diary.…”
Section: Resultsmentioning
confidence: 99%
“…Eight of the selected articles mentioned a practitioner’s assessment of the malocclusion, using the Dental Aesthetic Index (DAI) for five of them [ 7 , 9 , 33 , 34 , 39 ], the Aesthetic Component (AC) of the Orthodontic Treatment Need Index (IOTN) for four of them [ 8 , 9 , 30 , 31 ], associated with the Dental Health Component (DHC) of the IOTN for two of them [ 30 , 31 ] or with a patient’s self-perceived need for orthodontic treatment assessment using a modified IOTN-AC scale [ 8 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, previous studies found that orthodontic patients are more concerned with aesthetic and social issues than with interference with daily tasks [ 37 ]. However, some studies have shown no relationship between malocclusion and self-consciousness or shame [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“… 43 Apart from physical health, malocclusion, especially those leading to a poor facial appearance, affects children’s psychological health, forming low self-esteem. Increased overjet and deep bite, space between anterior teeth, and extremely misaligned teeth are potential reasons for children to be teased, 44 – 46 causing the affected person isolated from the social activities and difficult to interact with others.…”
Section: Definition and Risk Of Malocclusionmentioning
confidence: 99%